2015
DOI: 10.1371/journal.pone.0138009
|View full text |Cite
|
Sign up to set email alerts
|

Des-Aspartate-Angiotensin I Attenuates Mortality of Mice Exposed to Gamma Radiation via a Novel Mechanism of Action

Abstract: ACE inhibitors and ARBs (angiotensin receptor blockers) have been shown to attenuate radiation injuries in animal models of lethal gamma irradiation. These two classes of drug act by curtailing the actions of angiotensin II-linked inflammatory pathways that are up-regulated during gamma radiation in organ systems such as the brain, lung, kidney, and bone marrow. ACE inhibitors inhibit ACE and attenuate the formation of angiotensin II from angiotensin I; ARBs block the angiotensin AT1 receptor and attenuate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 37 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…Several phase I clinical trials have been conducted to evaluate the safety, tolerance and antitumor activity of intravenously administrated UAL. It was found that UAL was tolerable with manageable levels of toxicity, and could potentially improve remission rates in patients (Wang et al, 2013, 2015; Zhu et al, 2013; Qian et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Several phase I clinical trials have been conducted to evaluate the safety, tolerance and antitumor activity of intravenously administrated UAL. It was found that UAL was tolerable with manageable levels of toxicity, and could potentially improve remission rates in patients (Wang et al, 2013, 2015; Zhu et al, 2013; Qian et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…To confirm that oral DAA-I enters the systemic circulation in effective amounts and reaches its target, we anticipate a 2-week multi-dose phase I study of DAA-I that focuses on measuring PGE 2 and PGI 2 as surrogate biomarkers of DAA-I. This multi-dose study would hold much promise, as chronic oral administration of DAA-I 800 nmole/kg/day (0.95 mg/kg/day) to mice has been shown to cause a significant rise in plasma PGE 2 in the animals after 2 weeks of oral administration [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, DAA-I has been shown to be efficacious in animal models of cardiac hypertrophy [1], neointima formation [2], arteriosclerosis [2], renal failure [3], post-infarction injuries [4, 5], diabetes [6, 7], viral infection [8], chemical-induced inflammation [9], heat stroke [10], cancer [10] and gamma radiation lethality [11], where it has been found to significantly attenuate the severity of the pathology. At effective doses, DAA-I has no observable effects on the basal physiological and biochemical parameters that were measured in these studies and was found to lack secondary responses that could be considered adverse or side effects.…”
Section: Introductionmentioning
confidence: 99%
“…As a NF-κB pathway blocker and antioxidant, celastrol may represent a promising pharmacological agent with protective effects against gamma irradiation-induced injury. damage directly at a cellular level, or indirectly on water molecules, which then generate free radicals [1,2]. Free radicals further result in oxidation, DNA damage, and inflammation in the body [1,3,4].…”
mentioning
confidence: 99%
“…damage directly at a cellular level, or indirectly on water molecules, which then generate free radicals [1,2]. Free radicals further result in oxidation, DNA damage, and inflammation in the body [1,3,4]. Currently, the probability of radiation exposure in human beings is increased due to the wide use of nuclear energy in modern society, which makes the development of effective radioprotective agents an urgent task [5][6][7].Celastrol, also known as tripterine, is a pentacyclic triterpenoid that belongs to the family of quinone methides [8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%